Effects of replacing soybean meal with dried distillers grains with solubles on Boer-type goat growth performance and carcass traits - DeFisher, Jason R.; Crane, Alison R.; Lattimer, James M.; Jones, Cassandra K. (My University, 2018)
Goat producers typically use soybean meal (SBM) as the primary source of protein in diets for grower goats. However, little research has been done on the effects of feeding dried distillers grains with solubles (DDGS) as a cheaper alternative protein source. This experiment was designed to examine the effects of replacing increasing levels of SBM with DDGS on the growth performance and carcass traits of Boer-type goats. 48 goats (28.25 kg average body weight) were randomly sorted into 16 pens (3 goats/pen, 4 pens/treatment) and each pen was fed one of four diets based on the level of SBM replaced by DDGS (0%, 33%, 66%, or 100% replacement). The diets were fed for 47 days, and the goats and feeders were weighed every 7 days. At the end of the feeding period, final goat and feeder weights were collected before 2 goats from each pen were sent to slaughter. After slaughter hot carcass weight, carcass yield, loin eye area and depth, backfat depth, and body wall thickness were measured and collected. All data were analyzed using the PROC GLIMMIX version of SAS. Data for ADG, ADFI, and weekly body weight showed no significant differences. However, data for G:F showed an increased (P < 0.001) overall feed conversion ratio in goats fed 66% or 100% DDGS. This increased G:F ratio was driven by another significantly different G:F ratio for the period between days 21 and 28. This difference showed an increased (P < 0.035) feed conversion ratio in goats fed 66% DDGS compared to goats fed 0% DDGS. Post-slaughter data showed no significant differences in all carcass traits between goats fed 0% DDGS and goats fed any amount of DDGS. This data shows that DDGS can be used to replace SBM as a cheaper alternative with no differences or a slight increase in growth performance and no differences in carcass traits.
Keywords: Spring 2018